Analisis Perilaku Religiusitas Masyarakat Jabotabek di Era Pandemi Covid-19 - Dedi Junaedi; Faisal Salistia; Moh. Romli (Dakwatussifa: Journal of Da'wah and Communication, 2022)
The Covid-19 pandemic has had a multidimensional impact. This study aims to explore the impact of the Covid-19 pandemic on the people's economy. In particular, the academic community of IAI Nasional Laa Roiba Bogor. The research method used was descriptive-qualitative analysis method with a sample of the Laa Roiba Bogor National IAI academic community. The pandemic that lasted more than 15 months had a real impact on the economy of the people of Bogor Regency. Before the pandemic, there were people who felt their income decreased. However, the majority (60%) still claim that their income is relatively stable. After the pandemic, the majority of people (75%) experienced a decline in income. The pandemic has caused most people to experience a decrease in their monthly income of between 5-20%. The pandemic has made people try to find additional income through culinary businesses, part-time work, odd jobs, and providing consulting services. The pandemic has also shifted people's shopping patterns from traditional markets to online markets. Ready-to-eat food and basic necessities are the target of online shopping for the Bogor community. Keywords: Impact of the Covif-10 Pandemic, Community Income, Bogor Regency